2014
DOI: 10.4103/2229-5178.137772
|View full text |Cite
|
Sign up to set email alerts
|

Oral submucous fibrosis and its dermatological relation

Abstract: Oral submucous fibrosis is a chronic insidious disease and is well-recognized as a premalignant condition. It is a collagen related disorder associated with betel quid chewing and characterized by progressive hyalinization of the submucosa. The oral submucous fibrosis needs to be differentiated from scleroderma showing oral manifestations, as these diseases have different pathogenesis and prognostic aspects. The patients of oral submucous fibrosis can approach the dermatologist. The aim of this article is to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…It becomes difficult to retract or evert the lips, which transform into an elliptical shape. [5] Etiology of OSMF is areca nut, chilies, and micronutrient deficiencies of iron, zinc, and essential vitamins. Demonstration of various autoantibodies has given a possible autoimmune basis to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It becomes difficult to retract or evert the lips, which transform into an elliptical shape. [5] Etiology of OSMF is areca nut, chilies, and micronutrient deficiencies of iron, zinc, and essential vitamins. Demonstration of various autoantibodies has given a possible autoimmune basis to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Oral submucous fibrosis (OSMF) was first reported in the mid-20th century and was found in the oral cavity, with symptoms of idiopathic partial epithelial atrophy and sclerosis (Ali, Patil, Patil, & Prasant, 2014). OSMF is a potentially malignant oral disorder with a high risk of malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…It also reflects an autoimmune process in the oropharynx or a localized collagen disorder. 8 In advanced cases, trismus is the classical sequalae. Trismus cause problems in speech, oral hygiene, mastication and swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study in Karachi which included 325 patients, showed a strong association among labial bands in the fauces and buccal bands. 8 In some cases, fibrosis affects the soft palate and uvula whereas gingiva is relatively spared. Blockage of Eustachian tube causes hearing impairment and oesophageal fibrosis causes swallowing difficulty.…”
Section: Introductionmentioning
confidence: 99%